COVID‐19 in Patients With Inflammatory Arthritis: A Prospective Study on the Effects of Comorbidities and Disease‐Modifying Antirheumatic Drugs on Clinical Outcomes. Issue 12 (25th October 2020) - Haberman, Rebecca H.; Castillo, Rochelle; Chen, Alan; Yan, Di; Ramirez, Deborah; Sekar, Vaish; Lesser, Robert; Solomon, Gary; Neimann, Andrea L.; Blank, Rebecca B.; Izmirly, Peter; Webster, Dan E.; et al.
Abstract : Objective: To characterize the hospitalization and death rates among patients with inflammatory arthritis (IA) affected by coronavirus disease 2019 (COVID‐19) and to analyze the associations of comorbidities and immunomodulatory medications with infection outcomes. Methods: Data on clinical and demographic features, maintenance treatment, disease course, and outcomes in individuals with IA (rheumatoid arthritis and spondyloarthritis) with symptomatic COVID‐19 infection were prospectively assessed via web‐based questionnaire followed by individual phone calls and electronic medical record review. Baseline characteristics and medication use were summarized for hospitalized and ambulatory patients, and outcomes with the different medication classes were compared using multivariable logistic regression. Results: A total of 103 patients with IA were included in the study (80 with confirmed COVID‐19 and 23 with high suspicion of COVID‐19). Hospitalization was required in 26% of the participants, and 4% died. Patients who were hospitalized were significantly more likely to be older ( P < 0.001) and have comorbid hypertension ( P = 0.001) and chronic obstructive pulmonary disease ( P = 0.02). IA patients taking oral glucocorticoids had an increased likelihood of being admitted for COVID‐19 ( P < 0.001), while those receiving maintenance anticytokine biologic therapies did not. Conclusion: Among patients with underlying IA, COVID‐19 outcomes were worse in those receiving glucocorticoids but not in patients receiving maintenance anticytokine therapy. Further work is needed to understand whether immunomodulatory therapies affect COVID‐19 incidence.